2013
DOI: 10.1080/10548408.2013.810999
|View full text |Cite
|
Sign up to set email alerts
|

Emotions' Impact On Tourists' Satisfaction with Ski Resorts: The Mediating Role of Perceived Value

Abstract: and peacefulness -and a strong mediating role of overall perceived value between consumption emotions and satisfaction. Emotions related to "surprise" play no significant role in the evaluation of the ski resort experience. The present findings suggest that managers should focus on staging customers' stay at the resort to stimulate an emotional experience and position their packages based on the promise of such emotional experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 72 publications
1
15
0
1
Order By: Relevance
“…Despite the importance of emotions and perceived values in consumer behavior, relatively little attention has been paid to the relationship between these two variables, presumably because scholars continue to debate the nature of the relationship. Emotion is conceptualized as either an important antecedent [56,57] or a key outcome variable [58] of perceived value. Our view on these relationships is the former.…”
Section: Perceived Valuementioning
confidence: 99%
“…Despite the importance of emotions and perceived values in consumer behavior, relatively little attention has been paid to the relationship between these two variables, presumably because scholars continue to debate the nature of the relationship. Emotion is conceptualized as either an important antecedent [56,57] or a key outcome variable [58] of perceived value. Our view on these relationships is the former.…”
Section: Perceived Valuementioning
confidence: 99%
“…Nevertheless, regardless of the research stream on perceived value, what is generally accepted, as Rasoolimanesh et al () point out, is that a consumer's ‘overall assessment of a product or a service is a trade‐off between the benefits realized and the costs’ (p. 73). So, overall perceived value can be assessed by the overall evaluation of the experience in terms of benefits and sacrifices (Bonnefoy‐Claudet & Ghantous, ). An overall assessment of perceived value is not uncommon in tourism literature (Sabiote‐Ortiz, Frías‐Jamilena & Castañeda‐García, , , ; Bonnefoy‐Claudet & Ghantous, ; Phillips, Wolfe, Hodur & Leistriz, ; Chiu,Lee & Chen, 2014; Iniesta‐Bonillo, Sánchez‐Fernández & Jiménez‐Castillo, ; Lin & Kuo, ), and the same approach has been adopted in this research.…”
Section: Linking Ecotourism Knowledge and Ecotourist Satisfactionmentioning
confidence: 99%
“…Studies in the tourism context has suggested relationships between value and satisfaction (Bonnefoy-Claudet, & Ghantous, 2013), and between customer value and behavioral intentions (Chen & Chen, 2010;Chen & Tsai, 2008). So, based on the empirical studies in different tourist contexts, it is hypothesized that:…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%